Tinjauan Komprehensif Manajemen K3 Dan Kondisi Lingkungan Kerja Dalam Menjaga Kinerja Karyawan: Studi Kasus Pt Prolintas Transutama Logistik - Dimas Endriya Pratama; Didi Sunardi (Tamilis Synex: Multidimensional Collaboration, 2026)
Physical work environment conditions in maintaining employee performance at PT Prolintas Transutama Logistik. The method used is a qualitative approach with a descriptive case study method. Data collection was conducted through non-formal field observations and semi-structured interviews with 9 internal informants. The results indicate that OHS program implementation is not yet optimal, as indicated by an increasing trend in work incidents and a gap in fulfilling field Personal Protective Equipment (PPE), specifically a shortage of safety helmets and dust masks. On the other hand, the physical work environment experiences infrastructure constraints in the form of a deficit in office air conditioning (AC) units, leading to thermal discomfort, and limited operational manifest printers, causing long queues for printing Bill of Lading (B/L) documents. The accumulation of suboptimal safety guarantees and physical infrastructure discomfort directly implies reduced focus, job stress, and delays in customs clearance. Consequently, cargo distribution timeliness is disrupted, triggering customer complaints and causing annual sales turnover to fluctuate below the 100% target. Management is advised to accelerate PPE procurement, maintain office AC units, and add manifest printers.